Are hypohydrated older adults at increased risk of exhaustion?. Issue 1 (2nd October 2019) - Anjo, I.; Amaral, T. F.; Afonso, C.; Borges, N.; Santos, A.; Moreira, P.; Padrão, P.
Abstract: Background: Dehydration appears to affect muscle strength and weakness, although its influence on exhaustion remains unclear. The present study aimed to quantify the association between hydration status and exhaustion among older adults. Methods: A cluster sampling approach was used, representing Portuguese older adults (≥65 years) according to age, sex, education level and region within the Nutrition UP65 cross‐sectional study. A 24‐h urine sample was collected to estimate free water reserve (FWR), which was categorised into tertiles according to sex. Subjects with incomplete 24‐h urine and renal disease were excluded. From a sample size of 1500 subjects, 1143 were eligible. Exhaustion was self‐reported according to the Center for Epidemiologic Studies Depression Scale. A logistic regression model was conducted to evaluate the association between FWR and exhaustion. Odds ratios and the respective 95% confidence intervals were calculated by sex and age. Results: Free water reserve median (interquartile range) was 0.52 (0.68) L in women and 0.36 (0.77) L in men. Hypohydration affected 11.6% of women and 25.1% of men, whereas exhaustion was reported by 39.3% of women and 25.1% of men. After adjusting for confounders, women ≥80 years classified in the highest tertile of FWR showed a decreased risk of exhaustion (third tertile: odds ratio = 0.38; 95% confidence interval = 0.15–0.96) compared to women in the lowest FWR tertile. No such significant association was observed in women with <80 years and in men. Conclusions: These results show an association between worse hydration status and exhaustion in older women, highlighting the need to implement further studies clarifying this association.